Lost in translation: error analysis of texts translated from Arabic into English by Saudi translators - Alluhaybi, Maram (Frontiers in Education, 2024)
Biographic translation is crucial in today’s globalized world to preserve histories or shed light on the lives of people who influenced their nations or the world. The literature on biographic translation and the factors hindering such translation in an English as a foreign language (EFL) setting, especially in the Saudi context, is relatively limited. In the present study, the author analyzed the errors made by Saudi EFL learners when they translated a biography from Arabic into English. The data were drawn from a short text translated by female final-year university students as part of their course evaluations. The author conducted a qualitative analysis and classified errors according to Pospescu’s taxonomy. The results showed that the students committed all the three error types: linguistic, comprehensive, and translation. Within these three types, the students made diverse errors, ranging from misusing tenses to misspelling words. Consequently, their overall translations were unsatisfactory. This finding is helpful for both learners and educators, as the identified translation errors can be used as teaching aids in translation classes. The findings put emphasis on the importance of practice and prompt feedback as essential aids educators can use to support their students during their translation learning.